Peter Schäfer. Anziehung und Abstoßung: Juden und Christen in den ersten Jahrhunderten ihrer Begegnung / Attraction and Repulsion: Jews and Christians in the First Centuries of Their Encounter - Sievers, Joseph (Studies in Christian-Jewish Relations, 2016)
No abstract is available.